Analyzing the root of regional innovation performance in the European territory - Lopes, João M. (2021)
Submitted by Paulo Alexandre Anselmo Lopes daSilveira (paulo.silveira@ipcb.pt) on 2021-03-09T12:03:14Z No. of bitstreams: 1 AnalyzingtherootofregionalinnovationperformanceintheEuropeanterritory_2021_IJIS.pdf: 324923 bytes, checksum: afa08a796fffd3b517a205ce30ae2350 (MD5)